2022
DOI: 10.3390/molecules27238237
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect and the Potential Mechanism of Flavonoids and Phenolics of Moringa oleifera Lam. Leaves against Hyperuricemia Mice

Abstract: The aim of this study is to evaluate the anti-hyperuricemia effect and clarify the possible mechanisms of flavonoids and phenolics of MOL (MOL-FP) in mice. Hyperuricemia mice were generated via intraperitoneal (i.p.) administration of potassium oxonate (PO) and oral gavage (p.o.) of hypoxanthine (HX). Serum uric acid (UA), weight, serum XO activity, hepatic XO activity, urea nitrogen (BUN), creatinine (CRE), serum AST level, serum ALT level, mRNA expression of renal urate-anion transporter 1 (URAT1), glucose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…All tested plant materials contain phenolic and flavonoid groups. Flavonoids or phenolics groups have been reported to inhibit the action of the xanthine oxidase enzyme that converts purines into uric acid [28]. The conversion of hypoxanthine to xanthine by xanthine oxidase and guanase is a process that synthesizes |116 uric acid through the oxidative pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All tested plant materials contain phenolic and flavonoid groups. Flavonoids or phenolics groups have been reported to inhibit the action of the xanthine oxidase enzyme that converts purines into uric acid [28]. The conversion of hypoxanthine to xanthine by xanthine oxidase and guanase is a process that synthesizes |116 uric acid through the oxidative pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption is based on research that states that flavonoids and phenolic acid can mainly reduce uric acid levels in the serum of hyperuricemia rats by inhibiting xanthine oxydase activity and regulating urate transporters in the kidney. Flavonoids and phenolic acid prevent the pathological process of hyperuricemia by regulating biomarkers related to purine metabolism, amino acid metabolism, and lipid metabolism [28,30,39].…”
Section: Resultsmentioning
confidence: 99%
“…The above results indicated that Hsp also alleviated kidney injury in the HUA mice, but the protective effect of the Hsp-Cu (II) complex was significantly reinforced, while Alp only showed a weaker protective effect on the kidneys. Luo et al [38] also found that the renal protective effect of allopurinol was not as good as that of active ingredients from Moringa Oleifera Lam. leaves.…”
Section: Serum Physicochemical Indexes Of Hua Micementioning
confidence: 99%